2010
DOI: 10.1111/j.1365-2982.2009.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Motility of the oesophagus and small bowel in adults treated for Hirschsprung’s disease during early childhood

Abstract: This study demonstrates that adult patients with HD have preserved essential patterns of oesophageal and small bowel motility. However, abnormalities mainly characterized by increased contractile activity of the small bowel during fasting and postprandially are evident. These findings indicate alterations in neuronal control of motility and persistent involvement of the upper GI tract in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Data have shown that damage to the anal canal and a too low anastomosis cause fecal incontinence [19 , 20] . Since dysmotility in the upper gastrointestinal tract has been demonstrated in HD patients, it is not surprising that dysmotility also has been found in the remnant ganglionic colon [21][22][23] . A recent study found increased expression of protease-activated receptors in HD patients' colon that could be linked to inflammation, permeability and gut motility [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown that damage to the anal canal and a too low anastomosis cause fecal incontinence [19 , 20] . Since dysmotility in the upper gastrointestinal tract has been demonstrated in HD patients, it is not surprising that dysmotility also has been found in the remnant ganglionic colon [21][22][23] . A recent study found increased expression of protease-activated receptors in HD patients' colon that could be linked to inflammation, permeability and gut motility [24] .…”
Section: Discussionmentioning
confidence: 99%
“…A second group is children with continuing constipation and absent HAPCs, suggesting a neuropathy proximal to the aganglionic segment. It is worth noting that neuropathic motility abnormalities are seen in HD in esophagus, stomach, and small bowel of adults with HD treated in childhood (12,13). Therefore, it should come as no surprise that symptoms arise from motility problems in the remaining, presumably healthy colon.…”
Section: Discussionmentioning
confidence: 99%
“…A concomitant prevalence of esophageal and intestinal dysmotility has been described in several other entities, e.g. SSc [14,19], Hirschsprung's disease [20] and celiac disease [21]. Distinct esophageal and stomach physiologies, accompanied by different pathophysiology in esophageal dysmotility and gastroparesis, may explain the lack of association be-tween the two complications.…”
Section: Discussionmentioning
confidence: 99%